Optimizing to Minimize Thrust Force in Drilling Carbon Fiber Reinforced Plastic Composites with HSS Drill Bit Using Taguchi-Pareto Particle Swarm Optimization Method - Taiwo, Emmanuel Oluwatobi; Oke, Sunday Ayoola (Universitas Atma Jaya Yogyakarta, 2022)
In this study, a robust method of Taguchi-Pareto (TP) coupled with particle swarm optimization (PSO) is proposed to minimize the thrust force in the drilling of carbon fiber reinforced plastic composites. Taguchi-Pareto is used against Taguchi (T) to emphasize the prioritization scheme essential for deploying the resources to parameters. Besides, and differently from earlier studies, particle swarm optimization is integrated with the Taguchi-Pareto to optimize the structure further. A further result is placed in the fitness function of the PSO to cultivate the velocity and position vectors. In the TP-PSO, the Pareto scheme is introduced to prioritize the factors based on the 80-20-rule. The Taguchi method yielded a feasible optimal parametric setting. The TPSO and TPPSO attained minimum thrust force in four and seven iterations, respectively. Furthermore, the PSO, TPPSO, and TPSO hold the first, second, and third positions, respectively. Results suggest that the proposed robust TPPSO offers an important indicator of optimization of the thrust force while drilling carbon fiber reinforced plastic composites using existing datasets. The usefulness of this effort is to help drilling operators and process engineers undertake energy-saving decisions.